PKM WKI Kelurahan Malalayang I Timur tentang Eksplorasi dan Bahaya Jamur Patogen pada Ikan Mujair yang Siap Dipasarkan dan Dikonsumsi - Katili, Deidy Yulius; Umboh, Stella Deiby; Pontororing, Hanny H. (Jurnal Lentera: Penelitian dan Pengabdian Masyarakat, 2024)
Tilapia fish is much sought after by the lower middle class. The increasing public interest in tilapia fish is not accompanied by an increase in tilapia fish production. Tilapia fish production is often hampered by attacks by pathogenic fungi on tilapia fish. This pathogenic fungus also attacks tilapia fish that are ready to be marketed to consumers. The specific aim and target to be achieved in this PKM activity is to increase the knowledge and skills of WKI (Women) in exploring pathogenic fungi of tilapia fish that are ready to be marketed and consumed. To overcome the problem of mothers' lack of knowledge about the dangers of pathogenic fungi for tilapia fish, counseling methods and exploration training will be used and the dangers of pathogenic fungi for tilapia fish on human health. Based on the results of the analysis of participants' answers, it can be seen that there is an increase in the value in each measured value interval. In this final test, there were no longer any participants below the 50 score interval, in fact there were 3 people who could reach the score up to the 91-100 interval. The results of the analysis of the evaluation of learning topics found that there were no participants who did not understand the material provided by the guide. There were 7 participants who understood the material provided very well.